A Heterogeneous Branching Process with Immigration Modeling for COVID-19 Spreading in Local Communities in China. (22nd May 2021) - Zhang, Lin; Wang, Haochen; Liu, Zhongyang; Liu, Xiao Fan; Feng, Xin; Wu, Ye
Abstract : The COVID-19 pandemic spread catastrophically over the world since the spring of 2020. In this paper, a heterogeneous branching process with immigration is established to quantify the human-to-human transmission of COVID-19 in local communities, based on the temporal and structural transmission patterns extracted from public case disclosures by four provincial Health Commissions in China. With proper parameter settings, our branching model matches the actual transmission chains satisfactorily and, therefore, sheds light on the underlying COVID-19 spreading mechanism. Moreover, based on our branching model, the efficacy of home quarantine and social distancing are explored, providing a reference for the effective prevention of COVID-19 worldwide.